2011
DOI: 10.1021/jm2006904
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stereospecificity of 4,5-Disubstituted Oxazolidinone Ligands Binding to T-box Riboswitch RNA

Abstract: The enantiomers and the cis isomers of two previously studied 4,5-disubstituted oxazolidinones have been synthesized and their binding to the T-box riboswitch antiterminator model RNA investigated in detail. Characterization of ligand affinities and binding site localization indicate that there is little stereospecific discrimination for binding antiterminator RNA alone. This binding similarity between enantiomers is likely due to surface binding, which accommodates ligand conformations that result in comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Attempts to target T box riboswitches for development of antibiotic agents are in progress, but testing has focused on T box systems that regulate gene expression at the level of transcription attenuation (7,9). T box-targeted antibiotic compounds bind to the helix-bulge-helix structure of the antiterminator and prevent tRNA-dependent stabilization of the antiterminator, thereby leading to loss of downstream gene expression (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts to target T box riboswitches for development of antibiotic agents are in progress, but testing has focused on T box systems that regulate gene expression at the level of transcription attenuation (7,9). T box-targeted antibiotic compounds bind to the helix-bulge-helix structure of the antiterminator and prevent tRNA-dependent stabilization of the antiterminator, thereby leading to loss of downstream gene expression (7).…”
Section: Discussionmentioning
confidence: 99%
“…T box-targeted antibiotic compounds bind to the helix-bulge-helix structure of the antiterminator and prevent tRNA-dependent stabilization of the antiterminator, thereby leading to loss of downstream gene expression (7). A similar helix-bulge-helix structure is found in the Actinobacteria antisequestrator element, which would allow binding of the antibiotic compound and inhibition of translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23-30 Although significant advances have recently been made towards rationally designing small molecule ligands for RNA, 9,14,31-37 the limited available knowledge of the guiding principles of small molecule:RNA recognition has remained a significant hurdle. At the same time, some of the most successful screens have been conducted on RNA-targeted libraries generated by the diversification of molecular scaffolds known to interact with RNA, such as phenylbenzamidazoles, 38-40 oxazolidinones, 41-44 and diphenylfurans 45-47 though the library sizes and number of scaffolds tested has been fairly limited. 40,48 Based on these results, we see an urgent need for the identification and development of new RNA-targeted scaffolds that can expand scientists' repertoire for probing RNA structure and function, particularly RNA structures critical to infectious agents such as HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of oxazolidinone ligands binding to AM1A have indicated that even enantiomers can bind to the antiterminator RNA with similar affinity by making comparable binding contacts with different functional group partners. 17 Further studies are underway to characterize the specific binding interactions for the lead 1,4-disubstituted 1,2,3-triazoles binding to antiterminator model RNA AM1A. A key factor to determine is whether this series of compounds binds a single, common site or multiple sites within the T box riboswitch antiterminator RNA.…”
mentioning
confidence: 99%